LQR-Based Adaptive Virtual Synchronous Machine for Power Systems With High Inverter Penetration - Markovic, Uros; Chu, Zhongda; Aristidou, Petros; Hug, Gabriela (My University, 2019)
This paper presents a novel virtual synchronous machine controller for converters in power systems with a high share of renewable resources. Using a linear quadratic regulator-based optimization technique, the optimal state feedback gain is determined to adaptively adjust the emulated inertia and damping constants according to the frequency disturbance in the system, while simultaneously preserving a tradeoff between the critical frequency limits and the required control effort. Two control designs are presented and compared against the open-loop model. The proposed controllers are integrated into a state-of-the-art converter control scheme and verified through electromagnetic transient (EMT) simulations.
Keywords: Swing equation; Adaptive control; Linear-quadratic regulator (LQR); Virtual synchronous machine (VSM); Voltage source converter (VSC)